Capital flows and financial stability in emerging economies - Christopher F. Baum; Madhavi Pundit; Arief Ramayandi (Asian Development Bank (ADB), 2017)
There is mixed evidence for the impact of international capital flows on financial sector's stability. This paper investigates the relationship between components of gross capital flows and various financial stability indicators for 16 emerging and newly industrialized economies. Departing from panel data methods, for each financial stability proxy, we employ systems of seemingly unrelated regression estimators to allow variation in the estimated relationship across countries, while permitting crossequation restrictions to be imposed within a country. The findings suggest that, after controlling for macroeconomic factors, there are significant effects of different gross capital flow measures on the financial stability proxies. However, the effects are not homogeneous across our sample economies and across flows. Country-specific financial and macroeconomic characteristics help to explain some of these differences.
Keywords: E44; F41; 330; emerging economies; financial stability; international capital flows